Managing testicular torsion – time is of the essence. Issue 5 (25th September 2018) - Bastianpillai, Christopher; Ryan, Kate; Green, James SA
Abstract : Testicular torsion is a medical emergency that usually requires surgical intervention to untwist the spermatic cord and restore blood flow to the testis. Delays in the pathway from diagnosis to surgery can lead to testicular loss and need to be minimised. In this article the authors explore some of the current controversies surrounding the management of this important organ‐saving surgery.